الشيخ السالمي ومنهجه في الفتوى : دراسة مقارنة - حوسني، صالح سعيد هلال (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The subject of this thesis is the methodology of Sheikh AL Salmi in his fatwa rulings. It highlights the aspects of his intellectual, scientific and everyday life, and his role in social and political life in the Omani society. The study explores aspects of his fatwa rulings in the context of his position as Mufti, with a special interest in the sources that he relied upon, his approach to the various schools of thought, the differing lengths of his fatwa, and attempts to provide guidance in light of poor behavior and character. In many of his words, sheikh AL Salmi followed the descriptive, inductive and analytical approaches particularly where making comparison. Finally, the study analyze the way in which Sheikh Al Salmi drew upon methodologies to make his rulings. The study finds that although he followed the views of Ibadi school of thought in general. AL Salmi had on independent way of expressing his rulings and employing ijtihad. He rulings were always based on scholarly matters, not attempts to please people, whether the common man or rulers. His concern was the good of society, and to guide people in the way of Islam.